2020
DOI: 10.1101/2020.04.30.070383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulation in mTOR/HIF-1 signaling identified by proteo-transcriptomics of SARS-CoV-2 infected cells

Abstract: 26How Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infections engage 27 cellular host pathways and innate immunity in infected cells remain largely elusive. We 28 performed an integrative proteo-transcriptomics analysis in SARS-CoV-2 infected HuH7 cells to 29 map the cellular response to the invading virus over time. We identified four pathways, ErbB, 30 HIF-1, mTOR and TNF signaling, among others that were markedly modulated during the course 31 of the SARS-CoV-2 infection in vitro. Western bl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…Consistent with a robust signature for the glucocorticoid receptor across all CoVs (GR; q-values: SARS1, 3e-35; SARS2, 1e-35; MERS, 7e-32), while this paper was under review, studies were published showing the GR agonist dexamethasone was a successful therapeutic for SARS2 infection 31 . Finally, and also while this paper was under review, in vitro analyses confirmed our predictions of the modulation by SARS2 infection of ErbB/EGFR 20,32 and TGFBR 16,32 signaling systems (Fig. 2).…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Trasupporting
confidence: 77%
“…Consistent with a robust signature for the glucocorticoid receptor across all CoVs (GR; q-values: SARS1, 3e-35; SARS2, 1e-35; MERS, 7e-32), while this paper was under review, studies were published showing the GR agonist dexamethasone was a successful therapeutic for SARS2 infection 31 . Finally, and also while this paper was under review, in vitro analyses confirmed our predictions of the modulation by SARS2 infection of ErbB/EGFR 20,32 and TGFBR 16,32 signaling systems (Fig. 2).…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Trasupporting
confidence: 77%
“…Unfortunately, global and protein-specific surface glycosylation profiling is still challenging but could become an important future avenue to understand better how complex glycan patterns both of the virus as well as host cells determine the tropism of SARS-CoV-2. A rapidly rising number of reports on SARS-CoV-2 implicate intracellular phosphorylation events in a plethora of pathways from growth factor signaling to interferons and interleukins, HIF1A/mTOR signaling, PIKFYVE kinase inhibition, and JAK1 signaling ( 39 , 64 , 65 , 66 , 67 , 68 , 69 ), many of which are implicated in innate immunity. The full extent of phosphorylation regulation (or other PTMs for that matter) by SARS-CoV-2 remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1, which is hyperactive in LAM, promotes protein synthesis and cellular growth, and is believed to be used by SARS-CoV-2 to favor replication 13 . LARP1, an mTOR-regulated translational repressor, is among the 332 virus-interacting proteins identified by Gordon et al 11 , and Appelberg et al identified crosstalk between SARS-CoV-2 and mTOR/HIF-1 signaling 14 .…”
Section: To the Editormentioning
confidence: 99%